Moral bioenhancement, freedom and reason - Persson, I; Savulescu, J (Springer Netherlands, 2016)
In this paper we reply to the most important objections to our advocacy of moral enhancement by biomedical means – moral bioenhancement – that John Harris advances in his new book How to be Good. These objections are to effect that such moral enhancement undercuts both moral reasoning and freedom. The latter objection is directed more specifically at what we have called the God Machine, a super-duper computer which predicts our decisions and prevents decisions to perpertrate morally atrocious acts. In reply, we argue first that effective moral bioenhancement presupposes moral reasoning rather than undermines it. Secondly, that the God Machine would leave us with extensive freedom and that the restrictions it imposes on it are morally justified by the prevention of harm to victims.